Planning for climate-benign cities: Design of a mind map for smart energy transition - Karima Kourtit; Peter Nijkamp; Henk J. Scholten (Economic Themes, 2023)
Local energy transition initiatives - as part of a broader climate-benign and sustainability policy - have become a focal point of future-oriented resource and environmental strategies. Place-based energy conversion however, has turned out to be a very complicated task, from both a governance and research perspective. The present study seeks to sketch out the contours of local sustainable energy planning, with a particular emphasis on (i) practical data and evidence-based information requirements, (ii) the involvement and engagement of citizens and stakeholders, and (iii) the great research potential provided by digital information technology. To that end, a comprehensive mind map for energy transition is depicted, inspired by first experiments in the city of Rotterdam.
Keywords: R00; Q59; Q40; 330; energy transition; climate-benign cities; local energy mind map; citizen participation; Pentagon model; diabolo model; e-compass; digital tools; local energy scenario's